Implementation of Inquiry Learning Model on Students' Civics Learning Outcomes of Grade V Elementary School - Warye, Aulia; Waluyo, Lud; Aisyah, Iis Siti (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Ilmu Keguruan IAIN Manado, 2025)
This study examines the application of the inquiry learning model to the learning outcomes of Civic Education (PKn) of grade V students of SD Inpres I Tobelo, North Halmahera. This study was motivated by the low involvement and achievement of students in Civic Education learning. The inquiry learning model was applied to stimulate critical thinking, active participation, and student responsibility, which aims to improve their understanding of the concept of citizenship and foster democratic attitudes. This study used a qualitative descriptive approach, which included observation, interviews, and testing to assess the impact of the inquiry model. The findings showed a significant increase in student learning outcomes, with higher participation, better understanding of the concept of citizenship, and stronger critical thinking skills. This study contributes to educational practice by advocating inquiry-based learning as an effective strategy to engage students and improve educational outcomes, especially in remote areas such as North Halmahera.